Engineers' Self-Perceptions And A Strategy For Fostering Authentic Images of Engineers And Scientists Among Elementary School Students - McCann, Florence (My University, 2013)
Over a decade since Finson’s 2002 review article, “Drawing a Scientist: What We Do and Do Not Know After Fifty Years of Drawings”, images of scientists, sometimes stereotypes, continue to be created and promoted in popular media. The scholarly literature amply documents how education stakeholders ranging from elementary school age children to in-service teachers throughout the world perceive scientists. The impact of these images on students’ coursework and career choices is likewise well established. Strikingly, there are few studies where scientists reveal their self-perceptions. The most recent of these were published in 1975. The less well developed literature on engineer images reflects how they are stereotyped as “geeks” and “nerds”. No prior work on engineers’ self-perceptions has been identified. The engineering profession has explicitly recognized the importance of improving the image of engineering (Engineers Dedicated to a Better Tomorrow, 2006). Two research projects were initiated, a first to learn about the lived experiences of scientists, defined as faculty members in a natural science discipline at a research university holding a PhD and a second to learn about the lived experiences of engineers, defined as faculty members in a college of engineering at a research university, likewise holding a Ph.D. A naturalistic or constructivist research paradigm provided the theory base that guided the phenomenology research approach. No scientists agreed to join the scientist study. Engineer participants were asked to share their lived experiences as engineers in semi-structured in-person interviews. The interview data were analyzed according to a phenomenological reduction methodology (Moustakas, 1994). All identified protecting and serving society as an essential element of their experiences as engineers. Other themes that played significant roles in their experiences included their perceptions of the public; the public’s perception of engineers; stereotypes; gender; solitary work and team work; hard work/rigor; designing and building; solving problems; and creativity. While the engineers shared themes, they were not a monolithic group. Each had a unique underlying philosophy that governed how these themes were manifested. The engineers’ self-perceptions are valuable for designing interventions to foster accurate images of engineers for K-12 students. Curricula can be prepared that allow students to experience these essential aspects of being an engineer. The engineers’ Draw-An-Engineer Test (DAET) drawings can be used as benchmarks against which students’ drawings can be compared to assess the extent to which students’ perceptions of engineers and their work is aligned with that of these engineers’ self-perceptions. The themes described above guided the development of a curriculum for a STEM Club. The STEM Club was for identified gifted fifth grade girls. A female scientist/engineer led the club. The girls’ perceptions were accessed using the Draw-A-Scientist-Checklist (DAST-C) (Finson, et al., 1995); Enhanced-Draw-A-Scientist-Test (E-DAST) (Farland-Smith & McComas, 2009); and Draw-An-Engineer-Test (DAET) (Thompson et al., 2008; Knight & Cunningham, 2004) instruments administered before and after participation in STEM Club. The girls held well-developed, stable perceptions of scientists and drew traditional, predominantly male scientist images. After participation in STEM Club, they drew traditional images of scientists; however, female images increased by 30%. By contrast, the girls’ perceptions of engineers were far more plastic than their perceptions of scientists. By the last STEM Club meeting, they drew realistic images of engineers involved in design, laboratory investigation and testing activities. Female engineer images increased by 42%. These results suggest that a female scientist/engineer mentor in an informal club setting can have a significant impact on gifted fifth grade girls’ perceptions of scientist and engineer gender. STEM Club participation developed realistic perceptions of engineers among this group of fifth grade girls.
Keywords: Science Education